2011
DOI: 10.1115/1.4005411
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous and Semicrystalline Blends of Poly(vinylidene fluoride) and Poly(methyl methacrylate): Characterization and Modeling of the Mechanical Behavior

Abstract: After extensive studies starting in the 1970s in relation to miscibility and piezoelectric properties, the blends of poly(vinylidene fluoride) (PVDF) and poly(methyl methacrylate) (PMMA) have been revisited with the aim of assessing their mechanical behavior. Depending on the amount of PVDF, either amorphous or semicrystalline blends are produced. Typically, the blends remain amorphous when their PVDF content does not exceed 40 wt. %. Blend composition influence on the values of the glass transition temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Attention was paid on the decrease of both σ net max and δ(σ net max ) between 40 and 60%. Similar observations have already be done while considering the composition dependence of both yield stress and Young's modulus 9. They have been tentatively attributed to experimental difficulties accompanying polymer blending and blend processing.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Attention was paid on the decrease of both σ net max and δ(σ net max ) between 40 and 60%. Similar observations have already be done while considering the composition dependence of both yield stress and Young's modulus 9. They have been tentatively attributed to experimental difficulties accompanying polymer blending and blend processing.…”
Section: Resultssupporting
confidence: 79%
“…By increasing the PVDF content, these blends present a transition from amorphous to semicrystalline structure, which is likely to affect most mechanical properties. Right now, emphasis has been put on the stress–strain behavior of the blends in tension and compression7,8 over the low deformation range covering the elastic, anelastic, and viscoplastic response and molecular interpretations have been proposed 9. The aim of the present communication is to complement this analysis with the characterization of some failure properties, including toughness, in connection to blend relaxation and crystallization features.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…These authors also reported that the porosity of the film increases with increasing spinning rate as well as the agglomeration of the polymer on the surface of the substrate. On the contrary, at low spinning rate (500 rpm) the chain-folded fiber-type morphology, called spherulites [19][20][21][22]25,31], is observed by a surface analysis and it is attributed to the β phase. The influence of thermal annealing on the morphology of the spin-coated films was studied by Cardoso et al [34] and showed that the low evaporation rate of solution yields to the formation of pores.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the improvement of these latter phases content in a PVDF-based structure is highly recommended for the applications. There are variety of strategies to achieve the optimization of high polar content, like using mechanical stretching [18], applying a high electrical field during the elaboration [19], blending with polymethylmethacrylate (PMMA) homopolymer [21] or with PMMA-based block copolymer [22], doping the PVDF polymer matrix by inorganic nano-fillers [23,24] and by functionalizing these latter grafting specific molecules before their inclusion in the PVDF matrix [25,26]. However, using mechanical stretching and applying a high electrical field are only suitable for preparing self-standing films with thickness in a range of several µm and thus not suitable for standard Si-based technology.…”
Section: Introductionmentioning
confidence: 99%